The Influence of Capillary Geometry on the Stiffness of Hydrostatic Bearings in Medium-Sized Cylindrical Grinding Machines: A Simulation Analysis - Nguyen, Manh-Toan; Tran, The-Hung; Le, Duc-Do; Tran, Duc-Toan; Bui, Duy-Thinh; Tuan Anh, Bui (Engineering, Technology & Applied Science Research, 2024)
One of the most crucial parameters in the field of machine tool engineering is the stiffness of the machine tool spindle, as it has a direct impact on the precision and accuracy of machining. This paper presents a research on the effects of geometric parameters of capillary tubes, including diameter (dc) and length (lc), on the stiffness of hydrostatic bearings in machine tools. The oil pump pressure in this study was set at a range from 3 MPa to 5 MPa. The simulation results demonstrate the relationship between the capillary geometric parameters, pressure, and the stiffness of the hydrostatic spindle unit. These findings indicate a direct relationship between stiffness and pump pressure, with increases in pressure also raising lubricant temperature, which may impair cooling. The shape of the capillary directly affects the ratio of oil chamber pressure to pump pressure, which in turn affects hardness. The results of the study indicate that for spindles in machine tools, a dc ranging from 0.3 mm to 0.6 mm and a (lc/dc) ratio of between 20 and 100 are feasible based on the given stiffness requirement. It is possible to select an appropriate set of capillary parameters to achieve the best stiffness with specific requirements under the working conditions of hydrostatic bearings based on the results of the simulation analysis.